38.9k views
0 votes
Solve the equation by completing the square. 1) X^2 - 6x + 10 = 0

User Ayanda
by
6.7k points

1 Answer

1 vote

The given equation is


x^2-6x+10=0

First, we subtract 10 from each side


\begin{gathered} x^2-6x+10-10=-10 \\ x^2-6x=-10 \end{gathered}

Then, we divide the linear coefficient by half and elevated it to the square power.


((6)/(2))^2=3^2=9

Then, we add 9 on each side.


\begin{gathered} x^2-6x+9=-10+9 \\ \end{gathered}

Now, we factor the trinomial.


(x-3)^2=-1

At this point, we can deduct that the equation has no real solutions because there's no real number whose square power ends up in a negative number.

Hence, the equation has no solutions.

User Mark Andersen
by
5.6k points